IMPLEMENTING PERFORMANCE-BASED FORMATIVE ASSESSMENT IN GRAMMAR CLASS DURING REMOTE TEACHING - Titi Lestari; Dinar Martia Azizah (Universitas Wiralodra, 2021)
Language assessment is as challenging as language teaching. This idea applies more significantly in this Covid-19 pandemic situation as teachers struggle to create rich learning experiences to the learners remotely. In grammar class of higher education context, some problems have occurred especially when it comes to assessment, or, more specifically, giving appropriate tasks or tests. Observations on the writer’s online grammar class result in concerns around cheating and other barriers such as low internet connection, poor devices and unmonitored presence of students. The backwash effect of multiple-choice, standardized-like task is mostly negative. This is a Classroom Action Research proposing alternative assessment called performance-based assessment to better assess students’ grammar mastery. Online class observation, documentation and interview were employed to collect the data. Analysis model of Miles, Huberman, & Saldana (2014) is used. Performance-based assessment was implemented through some activities i.e. self-introduction paragraph, short diary, writing a message, reading short story, telling unexpected moments, and short interview. These tasks indicate to promote learners to be able to notice and apply features of grammar in communicative, natural, and realistic contexts of use.